(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the main types of risks that arise in the process of investment activities, their economic essence and impact on the activities of the enterprise. Mechanisms for identifying, assessing and effectively managing investment risks are considered. Also, methods of reducing risks used in various fields, including diversification, insurance, hedging and the use of modern financial instruments, are analyzed based on experience. The article substantiates the relevance of taking risks into account when making investment decisions and gives recommendations for minimizing risks.